Pratiques d’entreprises en santé et sécurité - Un panorama de la situation française depuis une double perspective, quantitative et qualitative - Thomas Amossé; Sylvie Célérier (Perspectives Interdisciplinaires sur le Travail et la Santé)
We provide a representative overview of how French firms put occupational risk prevention into practice. Even though the number of accidents and occupational diseases in this country remains an issue, precise information is not yet available despite the fact that firms are expected to play a crucial role in preventing risks. We used data from a statistical survey conducted in the mid 2000’s in France and from field work in the high-risk, poultry processing sector. Two outcomes are worthy of note. First, the hypothesis that the employers’ inertia explains the poor occupational-risk results in France should be reassessed somewhat. We attempt to elucidate the disparities between various companies’ practices and highlight the underlying reasons. Second, increasing regulatory injunctions and fines for firms that do not respect the law remains one possible way of improving occupational risk prevention. Indeed, we show that some companies, despite their own robust financial health, consciously ignore the law and their obligations concerning their employees’ health.